Effect of Forest Fragmentation on Fungal Diversity in Tropical Rainforests in Argentina - Díaz, Agustina (International Journal of Biology, 2024)
Purpose: To aim of the study was to analyze the effect of forest fragmentation on fungal diversity in tropical rainforests in Argentina. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on forest fragmentation in Argentina's tropical rainforests shows it significantly reduces fungal species diversity. Fragmented areas support fewer species than intact forests due to habitat loss and altered environmental conditions. Edge effects further exacerbate changes, favoring species adapted to disturbed habitats. Long-term effects continue to alter fungal community structure post-fragmentation. Conservation efforts must prioritize maintaining forest connectivity to mitigate these impacts on fungal diversity critical for ecosystem functioning in tropical rainforests. Unique Contribution to Theory, Practice and Policy: Met population theory, edge effects theory & intermediate disturbance hypothesis may be used to anchor future studies on effect of forest fragmentation on fungal diversity in tropical rainforests in Argentina. Implement habitat management practices that prioritize the preservation of large, contiguous forest patches to maintain fungal species richness and diversity. Advocate for policies that designate and protect large-scale forest reserves and corridors to conserve fungal biodiversity. Incorporate scientific findings into land-use planning and management strategies to ensure sustainable forest management practices that prioritize biodiversity conservation